Frequência de bruxismo em vigília e fatores associados: estudo transversal com avaliação ecológica momentânea - Silveira, Felipe Dantas (2024)
Awake bruxism (AB) is an activity of the masticatory muscles during wakefulness that is defined by repetitive or sustained tooth contact and/or by bracing or thrusting of the mandible. The aim of this study was to assess the mean percentage frequency (MPF) of AB behaviors using the Ecological Momentary Assessment (EMA) in a sample of adults, to investigate possible associated biopsychosocial factors and to compare the data generated using the EMA methodology with self-reported data obtained using the Oral Behaviors Checklist (OBC). A sample of 120 individuals aged between 20 and 50 was recruited. Participants answered sociodemographic questions, the OBC and psychosocial questionnaires on anxiety, stress, perfectionism, and coping. They also completed a 7-day diary on alcohol consumption, coffee consumption, and physical activity. AB behaviors were assessed by EMA via the smartphone app Bruxapp® over 7 days. In total, 114 patients completed the initial stages of the study, and 105 returned data from the app; however, 37 were excluded for not achieving a 60% daily response rate. The final sample comprised 68 patients, 38 of whom were female. The MPF of AB behaviors was 30.43%, with "teeth contact" being the most prevalent behavior at 15.84%. "Teeth grinding" was much less frequent, representing less than 1% of the total. Univariate analysis showed significant associations between AB and anxiety, stress, and alcohol consumption. However, in the multiple linear regression model, only anxiety (β = 1.72; p = 0.022) remained a significant predictor of AB frequency. No significant associations were found with gender, age, family income, coffee consumption, or physical activity. When analyzed individually, OBC questions 3, 4, and 5, which correspond to the AB behaviors described by Bruxapp®, showed significant agreement, but with Kendall correlations ranging from weak to moderate. Additionally, Bland-Altman analysis indicated that question 6 of the OBC tends to underestimate the occurrence of the behavior "mandible bracing". The two-level factorial structure of the OBC (awake) showed a better fit for predicting AB behaviors detected by EMA, as the non-functional activities (NFA) factor explained 31.14% of the total variance (r = 0.558; p < 0.001), while the functional activities (FA) factor explained, non-significantly, only 3.45% of the observed variance (r = 0.186; p = 0.128). In conclusion, AB is a frequent condition in the studied population, with anxiety being the main biopsychosocial factor to consider in its management. Additionally, using the NFA factor of the OBC may be useful as an initial screening of patients with possible AB, and the EMA strategy can be used instrumentally to confirm this diagnosis.